Knockout of a papain-like cysteine protease gene OCP enhances blast resistance in rice - Li, Yuying; Liu, Pengcheng; Mei, Le; Jiang, Guanghuai; Lv, Qianwen; Zhai, Wenxue; Li, Chunrong (Frontiers in Plant Science, 2022)
Papain-like cysteine proteases (PLCPs) play an important role in the immune response of plants. In Arabidopsis, several homologous genes are known to be involved in defending against pathogens. However, the effects of PLCPs on diseases that afflict rice are largely unknown. In this study, we show that a PLCP, an oryzain alpha chain precursor (OCP), the ortholog of the Arabidopsis protease RD21 (responsive to dehydration 21), participates in regulating resistance to blast disease with a shorter lesion length characterizing the knockout lines (ocp-ko). OCP was expressed in all rice tissues and mainly located in the cytoplasm. We prove that OCP, featuring cysteine protease activity, interacts with OsRACK1A (receptor for activated C kinase 1) and OsSNAP32 (synaptosome-associated protein of 32 kD) physically in vitro and in vivo, and they co-locate in the rice cytoplasm but cannot form a ternary complex. Many genes related to plant immunity were enriched in the ocp-ko1 line whose expression levels changed significantly. The expression of jasmonic acid (JA) and ethylene (ET) biosynthesis and regulatory genes were up-regulated, while that of auxin efflux transporters was down-regulated in ocp-ko1. Therefore, OCP negatively regulates blast resistance in rice by interacting with OsRACK1A or OsSNAP32 and influencing the expression profiles of many resistance-related genes. Moreover, OCP might be the cornerstone of blast resistance by suppressing the activation of JA and ET signaling pathways as well as promoting auxin signaling pathways. Our research provides a comprehensive resource of PLCPs for rice plants in defense against pathogens that is also of potential breeding value.